2021
DOI: 10.1002/cbin.11742
|View full text |Cite
|
Sign up to set email alerts
|

P2X7 receptor inhibition attenuates podocyte injury by oxLDL through deregulating CXCL16

Abstract: This study aims to evaluate the effect of purinergic ligand-gated ion channel 7 receptor (P2X7R) antagonist A438079 in kidneys of children with primary nephrotic syndrome (PNS). In vitro, human podocytes were respectively stimulated with oxLDL (80 µg/ml), A438079 (10 µmol/L), or the compound oxLDL and A438079 together.CXC chemokine ligand 16 (CXCL16) and P2X7R expression levels were detected by Western blot and immunofluorescence assay, respectively. Immunofluorescence assay was used to detect Dil-oxLDL, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
0
0
Order By: Relevance
“…It is generally accepted that oxidative modification of LDL results in loss of recognition by the LDL receptor and a shift to recognition by scavenger receptors, which do not have reduced surface expression when exposed to excess cholesterol [7]. It has been observed that scavenger receptors like CXCL16 are expressed on podocytes and may play a role in their apoptosis [8,9]. There is considerable evidence that oxLDL is a critical factor in the development of atherosclerosis and renal disease.…”
Section: Introductionmentioning
confidence: 99%
“…It is generally accepted that oxidative modification of LDL results in loss of recognition by the LDL receptor and a shift to recognition by scavenger receptors, which do not have reduced surface expression when exposed to excess cholesterol [7]. It has been observed that scavenger receptors like CXCL16 are expressed on podocytes and may play a role in their apoptosis [8,9]. There is considerable evidence that oxLDL is a critical factor in the development of atherosclerosis and renal disease.…”
Section: Introductionmentioning
confidence: 99%